Akurasi Keputusan dalam Penentuan Guru Berprestasi dengan Menggunakan Metode Simple Additive Weighting - W Wahyudi; Julius Santony; Gunadi Widi Nurcahyo (Jurnal Sistim Informasi dan Teknologi, 2020)
This study aims to obtain decision accuracy in determining teacher achievement using the Simple Additive Weighting method. Problems in Batam Muhammadiyah Vocational High School in determining the achievement of teachers using assessment criteria with the weight of educational qualifications, discipline, neatness, character, personality and teaching methods. The ranking process stage determines the alternatives of selected teacher achievement using the input of criteria weights. The results of this study get an accuracy rate of 80% with an accurate, fast, objective value. In the future, this research will be used as a new standard in determining teacher achievement.